10 kHz spinal cord stimulation vs. traditional low-frequency spinal cord stimulation for the treatment of diabetes peripheral neuropathic pain: study protocol for a multi-center randomized controlled clinical trial - Li, Chen; Liu, Chun-Hua; Li, Yi-Fan; Hu, Hui-Min; Shi, Qing; Liu, An-Xiang; Liu, Wen-Hui; Zhang, Yi; Mao, Peng; Fan, Bi-Fa (Frontiers in Neurology, 2025)
BackgroundDiabetic peripheral neuropathic pain (DPNP), affecting 50% of diabetes patients, imposes major burdens on quality of life and healthcare systems, while current therapies including pharmacotherapy and conventional spinal cord stimulation remain limited by insufficient efficacy and adverse effects. Our study aims to evaluate the clinical efficacy and safety of 10 kHz high-frequency spinal cord stimulation (HF-SCS) compared to traditional low-frequency SCS (T-SCS) in alleviating DPNP.MethodsThis prospective, randomized, controlled, multicenter trial will enroll 100 participants with DPNP. Patients aged 18–80 with chronic (≥6-month) lower limb pain will be randomly assigned to HF-SCS (10 kHz) vs. T-SCS (40–60 Hz). The primary outcome is the treatment efficacy rate, defined as ≥50% reduction in numeric rating scale (NRS) scores at 3 months post-intervention. Secondary outcomes include improvements in quality of life (Short Form 12), sleep quality (Athens Insomnia Scale), psychological status (Beck Depression Inventory), neuropathy severity (Michigan Neuropathy Screening Instrument), and microcirculatory parameters assessed via infrared thermography. Safety evaluations encompass adverse events, laboratory tests, and imaging findings.DiscussionThis study seeks to provide robust evidence on the superiority of HF-SCS in pain relief, functional improvement, and microcirculatory benefits, potentially establishing it as a preferred neuromodulation strategy for DPNP. Findings may advance clinical practice by addressing unmet needs in chronic pain management through targeted, mechanism-driven interventions.Clinical trial registrationhttps://www.chictr.org.cn/indexEN.html, identifier: ChiCTR2300078291.